Penggunaan Media Alphabet Board Untuk Meningkatkan Kemampuan Mengenal Huruf (Penelitian Tindakan Kelas Pada Anak Usia 5-6 tahun) - Putri Fauziah, Itsnawati; Nugraha, Dadan; Syafri, Herman (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study aimed to stimulate the letter recognition skills of children aged 5–6 years through the use of an alphabet board at RA Al-Ishlah, Tasikmalaya City. The background of this research stemmed from the low ability of children in recognizing letters, including letter symbols, sounds, and shapes. Moreover, the predominance of lecture-based methods and the lack of engaging learning media made children easily bored and less motivated to learn letters. This research employed a Classroom Action Research (CAR) design using the Kemmis and McTaggart spiral model, and it was conducted in two cycles. The subjects consisted of 13 students from group B1, including 5 boys and 8 girls. Data collection instruments included observation, field notes, and documentation. The results showed a significant improvement in the children’s letter recognition skills through the use of the alphabet board. This improvement was evidenced by the increase in average scores and learning mastery percentages from the pre-cycle to the second cycle. The percentage of children in the pre-cycle reached 32.69%, in cycle I, the percentage increased to 56.25%, and in cycle II, it reached 87.19%. The alphabet board proved effective as it combined learning and play activities, which made children more enthusiastic and motivated in recognizing letters. This study offered practical contributions to early childhood education, particularly in the application of fun and educational media to enhance children's language development